Preparation method of multicolor cobalt-nickel hydroxide electrochromic composite film layer
The introduction of V2O5 and a MnO2 connecting layer into Co(OH)2/Ni(OH)2 electrochromic films enhances color variability and bonding strength, addressing the limitations of existing Co(OH)2/Ni(OH)2 films by expanding color range and improving stability for practical applications.
Patent Information
- Application Number
- CN202411281532.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-13
AI Technical Summary
Existing Co(OH)2/Ni(OH)2 electrochromic films have limited variable colors and the film color is not bright enough, and they suffer from poor bonding with the substrate, affecting their cycle stability and practical applications.
A method for preparing a multi-color cobalt nickel hydroxide electrochromic composite film layer by introducing V2O5 into the surface of the film, and constructing a MnO2 connecting layer between the substrate and the Co(OH)2/Ni(OH)2 film to regulate the micro-nano structure, thereby increasing the bonding strength and stability.
The method results in a composite film with rich variable colors, improved bonding strength, and enhanced cycle stability, extending the color range from blue-green to orange-red and increasing the cycle stability by about 70%, suitable for applications in camouflage materials.
Smart Images

Figure CN119143406A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of electrochromic materials, and in particular to a method for preparing a multi-color cobalt-nickel hydroxide electrochromic composite film layer. Background Art
[0002] As a smart material, electrochromic materials have good application prospects in many fields including smart windows, adaptive camouflage, energy storage, etc. Electrochromic materials are divided into inorganic electrochromic materials and organic electrochromic materials. Inorganic electrochromic materials are the first electrochromic materials discovered and applied, mainly transition metal oxides and their derivatives. Cobalt and nickel oxides and hydroxides are a typical inorganic electrochromic material with the advantages of simple preparation process and good stability. Compared with inorganic electrochromic materials, organic electrochromic materials have faster response speed and richer colors. However, organic materials have poor chemical stability, are easy to degrade and are not resistant to high temperatures, so the research on organic electrochromic materials is still mainly in the laboratory stage.
[0003] In the reported studies, researchers have developed a variety of methods to prepare cobalt nickel oxide and hydroxide electrochromic films. YEFirat et al. prepared Cu-doped NiO film using constant current electrodeposition. The results showed that the Cu element can effectively improve the electrochromic properties of the NiO film (Electrochim. Acta (2019) 645-654). Nguyen Sy Pham et al. prepared NiO film using pulse electrodeposition. Compared with the NiO film prepared by the above-mentioned electrodeposition method, the performance was further improved (J. Appl. Electrochem. 52 (2022) 1343-1351). Kejun Xu et al. prepared NiO film using a hydrothermal method, showing excellent cycle performance, which is better than the film prepared by electrodeposition (Electrochim. Acta 441 (2023) 141812). Kyung Ho Kim used a simple one-pot hydrothermal method to prepare a Ni-Co oxide film on the FTO surface by adjusting the ratio of Ni and Co precursors. The film has a large light modulation amplitude and a low response time (Appl. Phys. A-Mater. 128 (2022) 507). Young-Hoon Lee developed a cathode constant current electrodeposition method to prepare Co(OH)2 / Ni(OH)2 electrochromic nanofilms. The preparation is rapid and can be completed within 1 minute. It has multiple color changes and a short response time, but the film layer has poor bonding with the substrate and is easy to fall off, which affects the cycle stability of the film layer and its feasibility in practical applications (Nano Energy 72 (2020) 104720). The cobalt nickel oxide and hydroxide electrochromic films reported above have fewer color changes and the film color is not bright enough.
[0004] Publication number: CN 117777992 A discloses a V2O5-based electrochromic material with rich color changes, but the preparation time is long and requires a high-temperature annealing process at 200°C. Publication number: CN 118270842 A discloses a method for preparing a modified vanadium oxide sol, which modifies the vanadium oxide sol by a silane coupling agent to obtain a modified vanadium oxide sol with high stability and high applicability, which can be used as an ion storage layer or electrochromic layer in an electrochromic device, but the preparation method of the vanadium oxide sol is relatively complicated. At the same time, a single V2O5 electrochromic film has many shortcomings such as poor electrochemical cycle stability, low film conductivity, small lithium ion diffusion coefficient, low contrast, poor coloring efficiency, and so on. Publication No.: CN107163928B discloses a tungsten trioxide / vanadium pentoxide core-shell nanowire array electrochromic material and a preparation method thereof. The preparation method uses FTO conductive glass containing a WO3 nanowire array film as a working electrode, dissolves vanadium sulfate, sodium dodecyl sulfate and sodium chloride in a mixed solution of anhydrous ethanol and deionized water as an electrodeposition solution, and performs cyclic voltammetry to deposit vanadium pentoxide on the working electrode, which is evenly coated on the tungsten trioxide nanorods, and the deposition of vanadium pentoxide does not destroy the initial structure of the tungsten trioxide nanowires.
[0005] There is no research in the prior art on the preparation process of Co(OH)2 / Ni(OH)2 / V2O5 ternary composite electrochromic film to solve the problem that the Co(OH)2 / Ni(OH)2 electrochromic film has few variable colors and the film color is not bright enough. Summary of the invention
[0006] In view of this, the present invention aims to propose a method for preparing a multi-color cobalt nickel hydroxide electrochromic composite film layer to solve the problem that the Co(OH)2 / Ni(OH)2 electrochromic film has fewer variable colors and the film color is not bright enough.
[0007] In the prior art, the Co(OH)2 / Ni(OH)2 electrochromic film is prepared by constant current electrodeposition, which has the advantage of rapid preparation and can be completed within 1 minute, greatly improving the production efficiency of the electrochromic film; however, the Co(OH)2 / Ni(OH)2 electrochromic film has the disadvantages of fewer variable colors and the film color is not bright enough.
[0008] In order to solve the above problems and enrich the variable colors of Co(OH)2 / Ni(OH)2 electrochromic film, the present invention creatively introduces V2O5 into the surface of Co(OH)2 / Ni(OH)2 electrochromic film to expand the variable color range from blue-green to orange-red; in the preparation, the Co(OH)2 / Ni(OH)2 electrochromic film produced by electrodeposition is used as the substrate, such as Figure 5As shown, the surface of the film is dense, and a micro-nano multidimensional stable structure is formed on the surface of the film during the deposition process. This structure can provide a larger specific surface area and more active sites for the deposition of V2O5, which helps to increase the deposition amount of V2O5, greatly reduces the diffusion path of Li+ in the film, and is very beneficial to the injection / extraction process of Li+ in the film; by regulating and optimizing the preparation parameters of V2O5, using simple cyclic voltammetry and electrodeposition methods, a simple and rapid preparation of multi-color Co(OH)2 / Ni(OH)2 composite films is achieved.
[0009] In the process of optimizing the preparation parameters of V2O5, the present invention adopts vanadyl sulfate, sodium dodecyl sulfate and sodium chloride dissolved in a mixed solution of anhydrous ethanol and deionized water as an electrodeposition solution, and performs cyclic voltammetry to deposit vanadium pentoxide on the working electrode; through a large number of experiments, after the Co(OH)2 / Ni(OH)2 electrochromic film is deposited and dried, the pH of the mixed solution is limited to the range of 2-4, and the voltage, scanning number and scanning speed of the cyclic voltammetry are controlled at the same time, so that the alkaline Co(OH)2 / Ni(OH)2 electrochromic film is used as the working electrode to precipitate V2O5 in an acidic solution, thereby realizing the preparation of the Co(OH)2 / Ni(OH)2 / V2O5 ternary composite electrochromic film.
[0010] At the same time, the present invention also constructs a MnO2 connecting layer between the substrate and the Co(OH)2 / Ni(OH)2 film to regulate the micro-nano structure of the film layer, thereby increasing the bonding strength between the film layer and the substrate, effectively ensuring its photoelectrochemical performance and stability in use, and forming a higher quality MnO2 / Co(OH)2 / Ni(OH)2 / V2O5 composite film with good bonding strength with the substrate.
[0011] The technical solution of the present invention is achieved in this way:
[0012] A method for preparing a multi-color cobalt-nickel hydroxide electrochromic composite film layer comprises the following specific steps:
[0013] S1: preparing a mixed solution of cobalt salt and nickel salt;
[0014] S2: Prepare Co(OH)2 / Ni(OH)2 electrochromic thin film; use constant potential deposition method, use Pt sheet or Pt mesh as counter electrode, and Ag / AgCl as reference electrode;
[0015] S3: After the deposition is completed, the surface is rinsed with deionized water and dried in an oven;
[0016] S4: preparing a mixed solution of the electrodeposition melt; adding VOSO4·H2O, sodium dodecyl sulfate, and NaCl to a mixed solution of anhydrous ethanol and deionized water, performing magnetic stirring, and adjusting the pH of the mixed solution to 2-4;
[0017] S5: using cyclic voltammetry to deposit the Co(OH)2 / Ni(OH)2 electrochromic film obtained in step S3 as the working electrode;
[0018] S6: After deposition, rinse the surface with deionized water and dry it in an oven.
[0019] Furthermore, in step S1, in the mixed solution of cobalt salt and nickel salt, the concentration of cobalt salt is 0.01-0.3 mol / L, and the concentration of nickel salt is 0.01-0.3 mol / L.
[0020] Furthermore, in step S1, the cobalt salt is one of CoSO4, Co(NO3)2·6H2O or CoCl2·6H2O, and the nickel salt is one of NiSO4, Ni(NO3)2·6H2O or NiCl2·6H2O.
[0021] Further, in step S2, the working electrode is one of FTO, ITO, FTO containing a MnO2 connecting layer, or ITO containing a MnO2 connecting layer.
[0022] Further, in step S2, the working electrode potential is between -0.3 and -1.2 V, and the deposition time is 2-80 s.
[0023] Furthermore, in step S3, the drying temperature is 40-90°C, and the drying time is 1-8h.
[0024] Further, in step S4, 1-9 g VOSO4·H2O, 0.05-0.6 g sodium dodecyl sulfate, and 0.3-1.0 g NaCl are added to a mixed solution of 100 mL anhydrous ethanol and deionized water, and magnetic stirring is performed for 0.1-3 h, and then the pH is adjusted to 2-4 with concentrated sulfuric acid.
[0025] Further, in step S5, the voltage is 0-3V, the number of scanning circles is 1-13 circles, and the scanning speed is 25-120mV / s.
[0026] Furthermore, in step S6, the drying temperature is 30-100° C., and the drying time is 5-15 hours.
[0027] Further, in step S2, the preparation method of FTO or ITO containing a MnO2 connecting layer comprises the following specific steps:
[0028] S1: preparing a mixed solution of manganese salt and sodium salt; in the mixed solution of manganese salt and sodium salt, the concentration of manganese salt is 0.02-0.2 mol / L, and the concentration of sodium salt is 0.02-0.2 mol / L;
[0029] S2: using constant potential deposition method;
[0030] S3: After deposition, rinse the surface with deionized water and dry it in an oven.
[0031] Compared with the prior art, the method for preparing a multi-color cobalt-nickel hydroxide electrochromic composite film layer of the present invention has the following advantages:
[0032] 1. The present invention sets up a preparation process to combine cobalt nickel hydroxide with electrochromic materials such as vanadium oxide, and by adjusting and optimizing V2O5 preparation parameters, a composite film with rich variable colors and excellent photoelectric properties can be obtained using simple cyclic voltammetry and electrodeposition methods, so that the variable color types of the prepared composite film layer are changed from the original blue-green to the current blue-green to orange-red range, showing richer color changes and higher color change efficiency.
[0033] 2. This preparation method can simply and quickly construct a MnO2 connecting layer, which can improve the bonding strength between the substrate and the Co(OH)2 / Ni(OH)2 film, so that the composite film has excellent photoelectric properties. While having a good light modulation amplitude and a fast response time, the cycle stability is correspondingly improved. The cycle stability is improved by about 70% compared with the material without MnO2, which has strongly promoted the engineering application of Co(OH)2 / Ni(OH)2 electrochromic film.
[0034] 3. The present invention provides a method for preparing a Co(OH)2 / Ni(OH)2 electrochromic film which is simple, rapid, has rich variable colors and strong stability, and can significantly improve the variable color range and cyclic stability of the electrochromic film layer, wherein the variable color range is extended from blue-green to orange-red, and the cyclic stability is improved by about 70% compared with the material without MnO2, which helps to promote the engineering application of Co(OH)2 / Ni(OH)2 electrochromic film as a camouflage stealth material (camouflage cover cloth, camouflage net, camouflage clothing, etc.).
[0035] 4. In the present invention, the Co(OH)2 / Ni(OH)2 electrochromic film is prepared by electrodeposition, the colorfulness of the film layer is increased by introducing the V2O5 component, and the micro-nano structure of the Co(OH)2 / Ni(OH)2 electrochromic film is regulated by introducing the MnO2 pretreatment layer, thereby improving the bonding strength between the Co(OH)2 / Ni(OH)2 electrochromic film and the substrate, thereby improving its cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0037] Figure 1 (a1-a3) are microscopic morphologies of Co(OH)2 / Ni(OH)2 / V2O5 electrochromic films, and (b1-b3) are microscopic morphologies of MnO2 / Co(OH)2 / Ni(OH)2 / V2O5 electrochromic films (MnO2 deposition time is 20s);
[0038] Figure 2 Optical photos of different samples at different potentials (MnO2 deposition time is 20s);
[0039] Figure 3 (a) and (b) are the light modulation amplitudes of Co(OH)2 / Ni(OH)2 / V2O5 electrochromic films, (c) and (d) are the light modulation amplitudes of MnO2 / Co(OH)2 / Ni(OH)2 / V2O5 electrochromic films (MnO2 deposition time is 10-30s);
[0040] Figure 4 (a) and (c) are the cycle stability of Co(OH)2 / Ni(OH)2 / V2O5 electrochromic films, (b) and (d) are the cycle stability of MnO2 / Co(OH)2 / Ni(OH)2 / V2O5 electrochromic films (MnO2 deposition time is 20s);
[0041] Figure 5 For Figure 5 (a) is the surface morphology formed by Co(OH)2 / Ni(OH)2 / V2O5, (b) is the EDS spectrum of Co(OH)2 / Ni(OH)2 / V2O5, (c) is the surface morphology formed by MnO2 / Co(OH)2 / Ni(OH)2 / V2O5 (MnO2 deposition time is 20s), (d) EDS spectrum of MnO2 / Co(OH)2 / Ni(OH)2 / V2O5 (MnO2 deposition time is 20s);
[0042] from Figure 6 This is the image of Mn-20s-co-CoNi after 2000 cycles of cyclic voltammetry, and the surface morphology after the upper film was broken. DETAILED DESCRIPTION
[0043] In order to make the technical means, objectives and effects of the present invention easy to understand, the embodiments of the present invention are described in detail below with reference to specific drawings.
[0044] It should be noted that all the terms used in the present invention to indicate directionality and position, such as "upper", "lower", "left", "right", "front", "back", "vertical", "horizontal", "inside", "outside", "top", "lower", "lateral", "longitudinal", "center", etc., are only used to explain the relative positional relationship and connection status between the components in a certain state, and are only for the convenience of describing the present invention, rather than requiring the present invention to be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the descriptions of "first", "second", etc. in the present invention are only used for descriptive purposes, and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features.
[0045] In the description of the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0046] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0047] The present invention discloses a method for preparing a multi-color cobalt-nickel hydroxide electrochromic composite film layer, which comprises the following specific steps:
[0048] S1: preparing a mixed solution of cobalt salt and nickel salt;
[0049] S2: Prepare Co(OH)2 / Ni(OH)2 electrochromic thin film; use constant potential deposition method, use Pt sheet or Pt mesh as counter electrode, and Ag / AgCl as reference electrode;
[0050] S3: After the deposition is completed, the surface is rinsed with deionized water and dried in an oven;
[0051] S4: preparing a mixed solution of electrodeposition melt; adding VOSO4 H2O, sodium dodecyl sulfate, and NaCl to a mixed solution of anhydrous ethanol and deionized water, performing magnetic stirring, and adjusting the pH of the mixed solution to 2-4;
[0052] S5: using cyclic voltammetry to deposit the Co(OH)2 / Ni(OH)2 electrochromic film obtained in step S3 as the working electrode;
[0053] S6: After deposition, rinse the surface with deionized water and dry it in an oven.
[0054] The present invention sets up a preparation process to combine electrochromic materials such as cobalt nickel hydroxide and vanadium oxide, and by adjusting and optimizing V2O5 preparation parameters, a composite film with rich variable colors and excellent photoelectric properties can be obtained using simple cyclic voltammetry and electrodeposition methods, so that the variable color types of the prepared composite film layer are changed from the original blue-green to the current blue-green to orange-red range, showing richer color changes and higher color change efficiency.
[0055] The preparation process of this preparation method is simple, controllable and easy to repeat. The film layer has good durability and stability, and can maintain its excellent electrochromic properties even under long-term use or harsh environments. The obtained composite film with rich variable colors and excellent photoelectric properties can be applied to a wider range of fields, expanding the application prospects of cobalt nickel hydroxide and vanadium oxide composite films.
[0056] Specifically, in step S1, in the mixed solution of cobalt salt and nickel salt, the concentration of cobalt salt is 0.01-0.3 mol / L, and the concentration of nickel salt is 0.01-0.3 mol / L.
[0057] The concentrations of cobalt salt and nickel salt in the technical solution are suitable for forming a uniform, dense and well-adhesive film, avoiding too low a concentration causing insufficient film thickness and affecting the electrochromic performance, while also preventing too high a concentration from affecting the deposition rate and uniformity of the film, so that the reaction proceeds within a reasonable speed range.
[0058] The concentration range of the cobalt salt and the nickel salt is obtained through experiments and practice, which makes the preparation process more reliable and easy to control, helps to improve the quality of the generated film and reduce production costs.
[0059] Preferably, the concentration of the cobalt salt is 0.02-0.2 mol / L, and the concentration of the nickel salt is 0.02-0.2 mol / L.
[0060] The cobalt salt and nickel salt concentration ranges set in this way can better balance the film formation quality, reaction speed and production cost, and help to quickly obtain high-quality Co(OH)2 / Ni(OH)2 electrochromic films.
[0061] Specifically, in step S1, the cobalt salt is one of CoSO4, Co(NO3)2·6H2O or CoCl2·6H2O, and the nickel salt is one of NiSO4, Ni(NO3)2·6H2O or NiCl2·6H2O.
[0062] The technical solution provides a variety of cobalt salts and nickel salts for selection. These salts can ionize the corresponding metal ions in the solution. The ionized Co 2+ and Ni 2+ Ions are the basis for the formation of Co(OH)2 / Ni(OH)2 electrochromic films. Different salts have different effects on the pH value, conductivity and other properties of the solution. By selecting suitable salts, the properties of the solution can be optimized, the deposition of the film can be improved, and the performance can be improved. Different salts may form films of different morphologies during the deposition process, such as flakes, spheres, etc. These morphologies will affect the electrochromic properties and adhesion of the film.
[0063] This setting provides a variety of cobalt and nickel salts to choose from, which can be flexibly matched according to specific needs. The composition, structure and performance of the film can be optimized according to the types and concentrations of different salts to meet specific application requirements, accelerate the deposition rate, improve preparation efficiency, and reduce energy consumption and material waste.
[0064] Specifically, in step S2, the working electrode is one of FTO, ITO, FTO containing a MnO2 connecting layer, or ITO containing a MnO2 connecting layer.
[0065] The working electrode in the technical solution can be selected from FTO or ITO according to actual needs. FTO is low in cost, resistant to high temperatures, has good chemical stability, can maintain stable performance in a variety of electrolytes, and is easy to mass produce and apply; ITO has high electrical conductivity, excellent light transmittance, and a smooth surface, which is conducive to the formation of a uniform and dense film and is suitable for the preparation of transparent electrochromic devices; FTO or ITO containing a MnO2 connecting layer can enhance the bonding force between FTO or ITO and Co(OH)2 / Ni(OH)2 film, while also improving the color change efficiency, broadening the color change range, and reducing maintenance and better costs.
[0066] This setting helps to form a variety of Co(OH)2 / Ni(OH)2 electrochromic films, adapting them to different application scenarios and expanding the scope of application of Co(OH)2 / Ni(OH)2 electrochromic films.
[0067] FTO and ITO are two common conductive glasses. FTO is the abbreviation of fluorine-doped tin oxide glass, and its main components are tin oxide and fluoride; ITO is the abbreviation of indium-doped tin oxide glass, and its main components are tin oxide and indium oxide.
[0068] Specifically, in step S2, the potential is between -0.3 and -1.2 V, and the deposition time is 2-80 s.
[0069] In the technical solution, the potential is set between -0.3 and -1.2 V, which can ensure that the cobalt ions and nickel ions in the solution undergo reduction reaction on the FTO, ITO or other working electrodes to form corresponding hydroxide films; setting a reasonable deposition time can ensure the thickness and uniformity of the film and prevent the electrochromic effect from being affected by too short or too long a time.
[0070] This setting can precisely control the formation, structure and properties of the film by adjusting the point position and deposition time, allowing researchers to customize films with specific electrochromic properties as needed, while achieving rapid deposition of the film, improving preparation efficiency, reducing energy consumption and costs, and forming a uniform, dense and highly adhesive film.
[0071] Preferably, the potential is between -0.5 and -1.0 V, and the deposition time is 5-60 s.
[0072] The setting of the potential and deposition time range can further improve the formation quality of the thin film and ensure the preparation efficiency.
[0073] Specifically, in step S3, the drying temperature is 40-90° C., and the drying time is 1-8 hours.
[0074] The drying temperature and time settings in the technical solution can remove moisture from the surface and inside of the film, preventing moisture from adversely affecting the film performance, while further improving the adhesion between the film and the conductive substrate and improving the stability of the film.
[0075] This drying temperature range keeps the electrochromic and optical properties of the film intact, helps to ensure the stability of the internal structure of the film, ensures the stability of the film quality, prevents the film from cracking or deforming, and improves its durability and service life.
[0076] Preferably, the drying temperature is 50-80° C. and the drying time is 1-6 h.
[0077] The setting of the drying temperature range and the drying time further improves the film drying quality, prevents film quality problems, and reduces production costs.
[0078] Specifically, in step S4, 1-9 g VOSO4·H2O, 0.05-0.6 g sodium dodecyl sulfate, and 0.3-1.0 g NaCl are added to a mixed solution of 100 mL anhydrous ethanol and deionized water, and magnetic stirring is performed for 0.1-3 h, and then the pH is adjusted to 2-4 with concentrated sulfuric acid.
[0079] In the technical solution, VOSO4·H2O is used as a vanadium source, and a vanadium compound V2O5 is introduced in the subsequent process to form a new layer on the surface of the Co(OH)2 / Ni(OH)2 electrochromic film, thereby broadening the color change range of the electrochromic film and enhancing the electrochromic performance of the film. VOSO4·H2O is easy to handle and has a high solubility in aqueous solution, so it is easy to prepare a uniform solution; sodium dodecyl sulfate can reduce the surface tension of the solution, improve the stability of the solution, prevent agglomeration or precipitation in the subsequent process, and ensure the preparation of a uniform solution; NaCl can adjust the ionic strength of the solution, affect the migration rate and distribution of ions in the solution, thereby indirectly affecting the deposition rate and morphology of the film and improving the conductivity of the solution.
[0080] The mixed solution of anhydrous ethanol and deionized water is used as a solvent to dissolve the above components and form a uniform solution. At the same time, it improves the fluidity of the solution and prevents the generation of bubbles during stirring or deposition. Magnetic stirring provides a simple and effective mixing method without complex equipment or operation, avoiding local concentration differences. Adjusting the pH value of the solution can optimize the reaction regulation of the solution and the deposition process of the film.
[0081] The electrodeposition solution of this arrangement has the ability to provide the vanadium source required for subsequent reactions, broaden the electrochromic properties of the film, ensure the uniformity and conductivity of the solution, and help to accurately control the reaction rate.
[0082] Preferably, 2-8 g VOSO4 H2O, 0.1-0.5 g sodium dodecyl sulfate, and 0.4-0.9 g NaCl are added to a mixed solution of 100 mL anhydrous ethanol and deionized water, magnetically stirred for 0.2-2 h, and then the pH is adjusted to 2-4 with concentrated sulfuric acid.
[0083] This setting further improves the uniformity and conductivity of the solution, and optimizes the reaction conditions of the solution and the deposition process of the thin film.
[0084] Specifically, in step S5, the voltage is 0-3V, the number of scanning circles is 1-13 circles, and the scanning speed is 25-120mV / s.
[0085] The voltage range, scanning number and scanning speed range of the cyclic voltammetry in the technical solution can accurately control the V2O5 deposition process on the surface of the Co(OH)2 / Ni(OH)2 electrochromic film, ensure the deposition rate and deposition thickness, and thus obtain a high-quality deposited layer with specific structure and performance.
[0086] This setting method is efficient and convenient, can complete V2O5 deposition in a short time, and the operation is relatively simple.
[0087] Preferably, the voltage is 0-2.7V, the number of scanning circles is 1-10 circles, and the scanning speed is 30-100mV / s.
[0088] This setup optimizes the electrochemical reaction rate and deposition thickness, further resulting in a higher performance deposited layer.
[0089] Specifically, in step S6, the drying temperature is 30-100° C., and the drying time is 5-15 hours.
[0090] The drying temperature and time settings in the technical solution can remove moisture from the surface and inside of the film, preventing moisture from adversely affecting the film performance, while further improving the adhesion between the film and the conductive substrate and improving the stability of the film.
[0091] This drying temperature range keeps the electrochromic and optical properties of the film intact, helps to ensure the stability of the internal structure of the film, ensures the stability of the film quality, prevents the film from cracking or deforming, and improves its durability and service life.
[0092] Preferably, the drying temperature is 50-80°C and the drying time is 6-12h.
[0093] The setting of the drying temperature range and the drying time further improves the film drying quality, prevents film quality problems, and reduces production costs.
[0094] Specifically, in step S2, the method for preparing FTO or ITO containing a MnO2 connecting layer comprises the following specific steps:
[0095] S1: preparing a mixed solution of manganese salt and sodium salt; in the mixed solution of manganese salt and sodium salt, the concentration of manganese salt is 0.02-0.2 mol / L, and the concentration of sodium salt is 0.02-0.2 mol / L;
[0096] S2: using constant potential deposition method;
[0097] S3: After deposition, rinse the surface with deionized water and dry it in an oven.
[0098] This preparation method can simply and quickly construct a MnO2 connecting layer, which can improve the bonding strength between the substrate and the Co(OH)2 / Ni(OH)2 film, so that the composite film has excellent photoelectric properties. While having a good light modulation amplitude and a fast response time, the cycle stability is correspondingly improved, which has strongly promoted the engineering application of Co(OH)2 / Ni(OH)2 electrochromic films.
[0099] Specifically, the manganese salt is selected from one of MnSO4 xH2O, Mn(NO3)2xH2O, and MnCl2 xH2O, and the sodium salt is selected from one of Na2SO4 and NaNO3.
[0100] The setting of a plurality of types of manganese salts and sodium salts facilitates the operator to select the type of salt in the specific solution according to actual conditions and needs, thereby expanding the application scope of the experiment.
[0101] Specifically, FTO or ITO is used as a working electrode, a Pt sheet or a Pt mesh is used as a counter electrode, Ag / AgCl is used as a reference electrode, the potential is between -0.5 and -1.0 V, and the deposition time is 5-60 s.
[0102] The working electrode in the technical solution can be selected from FTO or ITO according to actual needs. FTO is low in cost, resistant to high temperatures, has good chemical stability, can maintain stable performance in a variety of electrolytes, and is easy to mass produce and apply; ITO has high electrical conductivity, excellent light transmittance, and a smooth surface, which is conducive to the formation of a uniform and dense film and is suitable for the preparation of transparent electrochromic devices.
[0103] This setting can form FTO or ITO containing a MnO2 connecting layer, which helps to enhance the bonding force between FTO or ITO and the Co(OH)2 / Ni(OH)2 film, and construct a MnO2 connecting layer between the substrate and the Co(OH)2 / Ni(OH)2 film to regulate the micro-nano structure of the film layer, which can significantly improve the cycle stability of the electrochromic film layer, which is about 70% higher than that of materials without MnO2.
[0104] Specifically, the drying temperature is 50-80° C., and the drying time is 1-6 hours.
[0105] The drying temperature and time settings in the technical solution can remove moisture from the surface and inside of the film, preventing moisture from adversely affecting the film performance, while further improving the adhesion between the film and the conductive substrate and improving the stability of the film.
[0106] This drying temperature range keeps the electrochromic and optical properties of the film intact, helps to ensure the stability of the internal structure of the film, ensures the stability of the film quality, prevents the film from cracking or deforming, and improves its durability and service life.
[0107] Embodiment 1:
[0108] 1) Prepare 100 mL of a mixed solution of Co(NO3)2·6H2O and Ni(NO3)2·6H2O, where the concentration of Co(NO3)2·6H2O is 0.05 mol / L and the concentration of Ni(NO3)2·6H2O is 0.05 mol / L;
[0109] 2) Using constant potential deposition method, FTO was used as the working electrode, Pt sheet was used as the counter electrode, and Ag / AgCl was used as the reference electrode. The potential was -0.8 V and the deposition time was 20 s;
[0110] 3) After the deposition is completed, the surface is rinsed with deionized water and dried in an oven at a temperature of 60° C. for 6 h to obtain a Co(OH)2 / Ni(OH)2 electrochromic film;
[0111] 4) Take 3g VOSO4 H2O, 0.2g sodium dodecyl sulfate, and 0.6g NaCl and add them to a mixed solution of 50mL anhydrous ethanol and 50mL deionized water, stir magnetically for 0.5h, and then adjust the pH to 2.5 with concentrated sulfuric acid;
[0112] 5) Cyclic voltammetry was used for deposition, with FTO deposited with Co(OH)2 / Ni(OH)2 electrochromic thin film as the working electrode, the voltage was 0-2.7V, the number of scans was 5, and the scan rate was 100mV / s;
[0113] 6) After the deposition is completed, the surface is rinsed with deionized water and dried in an oven at a temperature of 60°C for 6 hours to obtain a Co(OH)2 / Ni(OH)2 / V2O5 film.
[0114] Embodiment 2:
[0115] 1) Prepare 100 mL of a mixed solution of Mn(NO3)2·6H2O and Na2SO4, where the concentrations of Mn(NO3)2·6H2O and Na2SO4 are 0.1 mol / L respectively;
[0116] 2) Use constant potential deposition method, use FTO as working electrode, Pt sheet as counter electrode, Ag / AgCl as reference electrode. Potential is between -0.7V, deposition time is 10s;
[0117] 3) After the deposition is completed, the surface is rinsed with deionized water and dried in an oven at a temperature of 50°C for 6 hours to obtain a MnO2 connection layer;
[0118] 4) Prepare 100 mL of a mixed solution of Co(NO3)2·6H2O and Ni(NO3)2·6H2O, where the concentration of Co(NO3)2·6H2O is 0.05 mol / L and the concentration of Ni(NO3)2·6H2O is 0.05 mol / L;
[0119] 5) Use constant potential deposition method, use FTO or ITO as working electrode, Pt sheet as counter electrode, Ag / AgCl as reference electrode. Potential is -0.8V, deposition time is 20s;
[0120] 6) After the deposition is completed, the surface is rinsed with deionized water and dried in an oven at a temperature of 60° C. for 6 h to obtain a MnO2-10 / Co(OH)2 / Ni(OH)2 electrochromic film;
[0121] 7) Take 3g VOSO4·H2O, 0.2g sodium dodecyl sulfate, and 0.6g NaCl and add them to a mixed solution of 50mL anhydrous ethanol and 50mL deionized water. Stir magnetically for 0.5h, and then adjust the pH to 2.5 with concentrated sulfuric acid;
[0122] 8) using cyclic voltammetry for deposition, using FTO deposited with Co(OH)2 / Ni(OH)2 electrochromic thin film as the working electrode, with a voltage of 0-2.7V, a scanning number of 5 circles, and a scanning rate of 100mV / s;
[0123] 9) After the deposition is completed, the surface is rinsed with deionized water and dried in an oven at a temperature of 60°C for 6 hours to obtain a MnO2-Co(OH)2 / Ni(OH)2 / V2O5 film.
[0124] The adjustable color and light modulation amplitude cyclic stability of Co(OH)2 / Ni(OH)2 / V2O5 and MnO2-Co(OH)2 / Ni(OH)2 / V2O5 electrochromic films were compared.
[0125] Depend on Figure 1 It can be seen that there are some particle deposits on the surface of the obtained Co(OH)2 / Ni(OH)2 / V2O5 and MnO2-Co(OH)2 / Ni(OH)2 / V2O5 electrochromic films, and the content of particle deposits on the surface of the latter is greater than that of the former. This indicates that the introduction of MnO2 may increase the deposition amount of V2O5.
[0126] Figure 2 These are optical photographs of different samples at different potentials. MnO2-Co(OH)2 / Ni(OH)2 / V2O5 has brighter colors, which means that there are more controllable colors.
[0127] Figure 3 The optical modulation amplitude of MnO2-Co(OH)2 / Ni(OH)2 / V2O5 with different deposition times of MnO2. It can be seen that compared with other deposition times, the optical modulation amplitude at 776nm is the largest at 27% when the deposition time of MnO2 is 20s.
[0128] from Figure 4 From the cyclic voltammetry curve results, it can be seen that the cycle stability of Co(OH)2 / Ni(OH)2 / V2O5 without MnO2 is poor, decaying to 70% after 400 cycles. Compared with it, the cycle stability of MnO2-Co(OH)2 / Ni(OH)2 / V2O5 is significantly improved. The charge storage capacity does not decay within 400 cycles and increases due to the long activation process.
[0129] from Figure 5 Among them, (a) is the image of the thin film formed by Co(OH)2 / Ni(OH)2 / V2O5, (b) is the EDS spectrum of Co(OH)2 / Ni(OH)2 / V2O5, (c) is the image of the thin film formed by Mn-20s-co-CoNi, and (e) is the EDS spectrum of Mn-20s-co-CoNi. These four pictures show that the protrusion is V.
[0130] from Figure 6 Image of Mn-20s-co-CoNi after 2000 cycles of cyclic voltammetry. After the upper film was broken, the bottom Mn-20s-co-CoNi-V film was exposed, indicating that the cobalt nickel hydroxide film did not dissolve in the acidic solution for depositing vanadium, and the micro-nano multi-dimensional stable structure of the cobalt nickel hydroxide film can provide a larger specific surface area and more active sites for the deposition of V2O5.
[0131] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a multi-color cobalt-nickel hydroxide electrochromic composite film layer, characterized in that: The specific steps include: S1: preparing a mixed solution of cobalt salt and nickel salt; S2: Prepare Co(OH)2 / Ni(OH)2 electrochromic thin film; use constant potential deposition method, use Pt sheet or Pt mesh as counter electrode, and Ag / AgCl as reference electrode; S3: After the deposition is completed, the surface is rinsed with deionized water and dried in an oven; S4: preparing a mixed solution of the electrodeposition melt; adding VOSO4·H2O, sodium dodecyl sulfate, and NaCl to a mixed solution of anhydrous ethanol and deionized water, performing magnetic stirring, and adjusting the pH of the mixed solution to 2-4; S5: using cyclic voltammetry to deposit the Co(OH)2 / Ni(OH)2 electrochromic film obtained in step S3 as the working electrode; S6: After deposition, rinse the surface with deionized water and dry it in an oven.
2. The method for preparing a multi-color cobalt-nickel hydroxide electrochromic composite film according to claim 1, characterized in that: In step S1, in the mixed solution of cobalt salt and nickel salt, the concentration of cobalt salt is 0.01-0.3 mol / L, and the concentration of nickel salt is 0.01-0.3 mol / L.
3. The method for preparing the multi-color cobalt nickel hydroxide electrochromic composite film layer according to claim 2, characterized in that: In step S1, the cobalt salt is one of CoSO4, Co(NO3)2·6H2O or CoCl2·6H2O, and the nickel salt is one of NiSO4, Ni(NO3)2·6H2O or NiCl2·6H2O.
4. The method for preparing a multi-color cobalt-nickel hydroxide electrochromic composite film layer according to claim 1, characterized in that: In step S2, the working electrode is one of FTO, ITO, FTO containing a MnO2 connecting layer, or ITO containing a MnO2 connecting layer.
5. The method for preparing a multi-color cobalt-nickel hydroxide electrochromic composite film according to claim 4, characterized in that: In step S2, the working electrode potential is between -0.3 and -1.2 V, and the deposition time is 2-80 s.
6. The method for preparing a multi-color cobalt-nickel hydroxide electrochromic composite film layer according to claim 1, characterized in that: In step S3, the drying temperature is 40-90°C, and the drying time is 1-8 hours.
7. The method for preparing a multi-color cobalt-nickel hydroxide electrochromic composite film according to claim 1, characterized in that: In step S4, 1-9 g VOSO4·H2O, 0.05-0.6 g sodium dodecyl sulfate, and 0.3-1.0 g NaCl are added to a mixed solution of 100 mL anhydrous ethanol and deionized water, and magnetic stirring is performed for 0.1-3 h, and then the pH is adjusted to 2-4 with concentrated sulfuric acid.
8. The method for preparing a multi-color cobalt-nickel hydroxide electrochromic composite film layer according to claim 1, characterized in that: In step S5, the voltage is 0-3V, the number of scanning circles is 1-13 circles, and the scanning speed is 25-120mV / s.
9. The method for preparing a multi-color cobalt-nickel hydroxide electrochromic composite film according to claim 1, characterized in that: In step S6, the drying temperature is 30-100°C and the drying time is 5-15h.
10. The method for preparing a multi-color cobalt-nickel hydroxide electrochromic composite film according to claim 4, characterized in that: In step S2, the preparation method of FTO or ITO containing a MnO2 connecting layer comprises the following specific steps: S1: preparing a mixed solution of manganese salt and sodium salt; in the mixed solution of manganese salt and sodium salt, the concentration of manganese salt is 0.02-0.2 mol / L, and the concentration of sodium salt is 0.02-0.2 mol / L; S2: using constant potential deposition method; S3: After deposition, rinse the surface with deionized water and dry it in an oven.
Citation Information
Patent Citations
Tungsten trioxide / vanadium pentoxide core-shell-structured nanowire array electrochromic material and preparation method thereof
CN107163928A
Preparation method of multi-color electrochromic thin film with tin dioxide / vanadium pentoxide core-shell structure
CN109881198A
Electrochromic composite film with high cycling stability and preparation method thereof
CN117776547A
Process for producing hybrid nano-filament electrodes for lithium batteries
US20090269511A1
Improved process of ultrasonic spray pyrolysis deposition of one or more electrochromic and / or electrolytic films on a substrate
US20170363928A1
Cited By
Method for constructing complementary electrochromic device based on nickel-cobalt double-metal hydroxide film
CN121325478A
